OBSTACLES AND STRATEGY OF MUNICIPAL ISLAMIC BONDS ISSUANCE AS AN ALTERNATIVE OF MUNICIPAL FUNDING - Asa Jasmine Harimurti; Achmad Zaky (AFEBI Islamic Finance and Economic Review, 2018)
The objective of this thesis is to identify obstacles and strategies for municipal Islamic bond issuance as an alternative in regional financing using the Analytical Networking Process (ANP). The analysis found that the most dominant obstacle in the aforementioned issue is the local government aspect. In the aspect of the central government, the obstacle is the unavailability of studies concerning the instrument of municipal Islamic bonds. In the aspect of the local government, the obstacle is the low understanding of the government about the means of municipal Islamic bonds. In the aspect of the regional house of representative, the obstacle is the behaviour of representatives, in which they complicate bureaucracy in the issuance of municipal Islamic bonds. The most dominant solution for the obstacles and strategy in the issuance of municipal Islamic bonds is a fundamental solution. The dominant strategy for a fundamental solution is the socialization of education about municipal Islamic bonds and a promotion pattern in collaboration with Indonesia’s financial service authority.Keywords: municipal Islamic bonds, obstacle, strategy